Healthcare Costs and Medication Adherence Among Patients with Fibromyalgia: Combination Medication vs. Duloxetine, Milnacipran, Venlafaxine, and Pregabalin Initiators. Issue 2 (28th May 2017) - Marlow, Nicole M.; Simpson, Kit N.; Vaughn, Ivana A.; Jo, Ara; Zoller, James S.; Short, Edward B.
Abstract: Objective: To examine medication adherence and healthcare costs for combination prescription initiators (duloxetine/milnacipran/venlafaxine with pregabalin) vs. monotherapy initiators (duloxetine, milnacipran, venlafaxine, and pregabalin) among patients with fibromyalgia syndrome (FMS). Methods: Our retrospective cohort study used claims data for the South Carolina Blue Cross Blue Shield State Health Plan (SHP). Patients with FMS ≥ 18 years of age, with prescription initiation from July 1, 2007, through June 30, 2010, and SHP enrollment for 12 months pre‐ and post‐index periods were included (combination: n = 100; pregabalin: n = 665; duloxetine: n = 713; milnacipran: n = 131; venlafaxine: n = 272). Medication adherence measures included high adherence (medication possession ratio ≥ 80%) and total supply days. Healthcare costs comprised direct medical expenditures. Propensity score methods of inverse probability of treatment weights were used to control for selection bias due to differing pre‐index characteristics. Results: Odds ratios for high adherence were significantly increased ( P < 0.05) among the combination cohort vs. the venlafaxine (2.15), duloxetine (1.39), and pregabalin (2.20) cohorts. Rate ratios for total supply days were significantly higher ( P < 0.05) for combination vs. venlafaxine (1.23), duloxetine (1.08), and pregabalin (1.32) cohorts. Expenditures for total health care were significantly higher ( P < 0.05) for combination vs. duloxetine ($26, 291 vs. $17, 190), milnacipran ($33, 638 vs. $22, 886), and venlafaxine ($26, 586 vs. $16, 857) cohorts. Conclusions: Medication adherence was considerably better for combination prescription initiators; however, expenditures for total health care were higher. Still, our findings suggest important clinical benefits with the use of combination prescription therapy, and prospective studies of medication adherence are warranted to examine causal relationships with outcomes not captured by healthcare claims databases.